Peran Guru Pendidikan Agama Islam dalam Internalisasi Nilai-Nilai Keislaman pada Siswa Down Syndrome: Studi di SLB Negeri Tenggarong - Isna Radiyah; Maryam; Sheva Hero Christian; Niya Armita Sari; Arbiah; Rani Aulia (CV. Ulil Albab Corp, 2026)
The need for tailored educational services for students with special needs, particularly in character and spiritual development through Islamic Religious Education (PAI), is the primary foundation of this study. This research aims to analyze how PAI teachers carry out their duties, understand the learning strategies implemented, identify obstacles encountered, and evaluate efforts to optimize the instillation of Islamic values ​​in Down Syndrome students at Tenggarong State Special Needs School. Using a qualitative descriptive case study method, data collection was conducted through structured interviews, direct observation, and document review. The findings indicate that PAI teachers play a crucial role as supporters, guides, and role models for students. The strategies used are multisensory and flexible, including demonstration techniques, repetition-based teaching, and the integration of visual media and music to address students' cognitive limitations. Key obstacles include short-term memory difficulties and low focus, which are addressed through a compassionate, emotionally nurturing approach and individualized content adjustments. The study concludes that the success of value instillation is largely determined by consistent daily routines and close collaboration with parents. These results provide a valuable contribution to the development of an inclusive and humanistic-oriented model of religious education.